2013
DOI: 10.1179/1743281212y.0000000094
|View full text |Cite
|
Sign up to set email alerts
|

Methodology based on genetic optimisation to develop overall parsimony models for predicting temperature settings on annealing furnace

Abstract: Developing better prediction models is crucial for the steelmaking industry to improve the continuous hot dip galvanising line (HDGL). This paper presents a genetic based methodology whereby a wrapper based scheme is optimised to generate overall parsimony models for predicting temperature set points in a continuous annealing furnace on an HDGL. This optimisation includes a dynamic penalty function to control model complexity and an early stopping criterion during the optimisation phase. The resulting models (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Chen et al [32] also use an evolutionary approach to simultaneously optimize complexity and weights of learning vector quantification networks for bankruptcy prediction. Sanz et al [8] reported a novel GA-based optimization to create better overall parsimonious ANNs for predicting setpoints in an annealing furnace of a steel galvanizing industrial plant.…”
Section: Related Research On Parsimonious Modeling With Soft Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [32] also use an evolutionary approach to simultaneously optimize complexity and weights of learning vector quantification networks for bankruptcy prediction. Sanz et al [8] reported a novel GA-based optimization to create better overall parsimonious ANNs for predicting setpoints in an annealing furnace of a steel galvanizing industrial plant.…”
Section: Related Research On Parsimonious Modeling With Soft Computingmentioning
confidence: 99%
“…Developing parsimonious models presents a promising approach [7][8][9][10]. According to the parsimony criterion, the model with the least complexity that performs with similar accuracy is always preferred.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of historical data with this new configuration prevented the design of the new thermal cycles using data-driven models [9], thus the migration was progressive: for each cycle, first it was made an adjustment using simulations tools and lab tests with the Rhesca ® galvanizing simulator, then every new cycle had to be checked during one or more scheduled trials in the line before to be approved for its industrial use.…”
Section: Case Studymentioning
confidence: 99%